Anticarbamazepine antibody induced by carbamazepine in a patient with severe serum sickness. Issue 6 (June 1991) - Hosoda, N; Sunaoshi, W; Shirai, H; Bando, Y; Miura, H; Igarashi, M
Abstract : Anticarbamazepine antibody was detected in a patient who had clinical signs of serum sickness induced by carbamazepine. Skin rash, fever, oedema, and lymphadenopathy are classic signs of severe adverse reaction, but although immunological hypersensitivity is thought to be a contributory factor, the presence of anticarbamazepine antibody has not previously been reported to our knowledge.